Religion as "universal obsessional neurosis of humanity"? Re-reading Freud on religion - Kistner, Ulrike (HTS teologiese studies, 2021)
In his writings on culture, Freud stipulates a close relation between religion and psychopathology, and obsessional neurosis in particular. In this article, I would like to explore the nature of that relation. How is it articulated, and how is it transformed in the course of Freud’s work over four decades, between 1894 and 1939? (How) can cultural (i.e. by definition, collective) phenomena be understood on the basis of symptoms described for individual psychology? On what basis can categories of individual psychology be extended to the analysis and history of cultural and societal formations? What perspectives can psychopathology open up for the analysis of culture? Is religion ‘the cure’, or ‘the symptom’? Or are there grounds for breaking open the relation between psychopathology and religion as it has increasingly solidified in the course of Freud’s work, and has been hotly contested ever since? This article works its way through these questions, and proposes to open some paths of investigation on the subject that are inherent in psychoanalytic theory, but have been prematurely closed off by Freud himself, as well as his adepts and critics.Contribution: This article critically engages with Freud’s most (in)famous statements on the relation between psychopathology and religion through an exposition of the articulations of this relation, as they change with the introduction of particular concepts and theories.